Knowledge, adherence and quality of life among type 2 diabetes mellitus Patients (2019)
Type 2 diabetes mellitus is a chronic disease that can be controlled to improve quality of life. The aims of this study were to analyze the relationship between knowledge, adherence and quality of life in diabetic patients. A cross-sectional survey was conducted in the out-patients department of Regional Hospital in Bantul, Yogyakarta Province, Indonesia. Data were collected between September and October 2017 using quota sampling. Knowledge was assessed using DKQ 24, adherence was assessed using ProMAS, while quality of life was assessed using EQ-5D-5L. Of total 200 patients, majority were female (58%), age ≥ 60 years (61.5%), unemployed (66.5%), first grade education (39%), monthly income > IDR 2 million (38.5%), diagnosed DM type 2 for 5-10 years (36%), without complication (68%), consume 4-6 drugs (57%), prescribed combination of oral and insulin (46.5%) and experienced of adverse events (55%). Patients were in the moderate knowledge (61%), moderate to high adherence (47.5%) and the average of patient's utility score was 0.793 with the biggest problem was on the pain/discomfort dimension. There is relationship between gender, education, income and duration of diagnosed type 2 DM with knowledge level (p<0.05). The relationship between gender, complications and number of drugs with quality of life was found (p <0.05). Adherence was also related to quality of life (p<0.01) and correlation coefficient of 0.307. These results indicate that health care personnel still need to pay attention on factors influence the level of knowledge, adherence and quality of life.